2016
DOI: 10.1007/s12046-016-0498-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors causing cost overrun of the construction projects in India

Abstract: Delay and cost overrun are common phenomena in projects worldwide. However, these are especially severe in developing countries. In India as per MOSPI report, 235 projects out of 410 were severely affected cost overrun due to certain factors. A short questionnaire was conducted with 15 prominent factors responsible for cost overrun and forwarded to 190 constructional professionals across India. Total 85 responses were received and it was analyzed using various statistical tools such as analysis of variance (AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Comparison among the studies showed that main causative factors of cost variation in this study and the study of Wanjari et al [16] is same i.e Fluctuations in cost of materials. The main factors of cost variation in the study of Kim et al [15] and Allahaim et al [18] is additional work and market changes respectively.…”
Section: Table 4 Comparisons With Previous Studiessupporting
confidence: 66%
See 4 more Smart Citations
“…Comparison among the studies showed that main causative factors of cost variation in this study and the study of Wanjari et al [16] is same i.e Fluctuations in cost of materials. The main factors of cost variation in the study of Kim et al [15] and Allahaim et al [18] is additional work and market changes respectively.…”
Section: Table 4 Comparisons With Previous Studiessupporting
confidence: 66%
“…The main factors of cost variation in the study of Kim et al [15] and Allahaim et al [18] is additional work and market changes respectively. Planning related factor in ranked 2 nd in both this study and the study of Wanjari et al [16]. Design related causative factors of cost variation is more frequent in the study of Allahaim et al [18] while none of the top five factors is related to design in this study and Kim et al [15].…”
Section: Table 4 Comparisons With Previous Studiessupporting
confidence: 45%
See 3 more Smart Citations